Further Understanding on International Student Mobilities in Asia is Needed - Pham, Hiep-Hung (Journal of International Students, 2022)
Despite becoming a growing hub of international students, Asia appears to receive insufficient attention from researchers in the field of international education and student mobilities. This editorial is a call for attention from colleagues in the international education community to prioritize ISM in Asia in their research agendas, including comparative research across countries and regions. It recommends implications for stakeholders and potential avenues for future studies on ISM in Asia.